2015
DOI: 10.2967/jnumed.114.146308
|View full text |Cite
|
Sign up to set email alerts
|

MR-Based Attenuation Correction Using Ultrashort-Echo-Time Pulse Sequences in Dementia Patients

Abstract: Attenuation correction (AC) is a critical requirement for quantitative PET reconstruction. Accounting for bone information in the attenuation map (μ map) is of paramount importance for accurate brain PET quantification. However, to measure the signal from bone structures represents a challenging task in MR. Recent 18 F-FDG PET/MR studies showed quantitative bias for the assessment of radiotracer concentration when bone was ignored. This work is focused on 18 F-FDG PET/MR neurodegenerative dementing disorders. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
59
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 32 publications
(41 reference statements)
2
59
1
Order By: Relevance
“…The creation of such parametric images can be divided into [208], (E) Anazodo et al [209], (F) Izquierdo-Garcia et al [210], (G) Burgos et al [211], (H) Merida et al [212]; MLAA-based methods: (I) Benoit et al [213]; Segmentation-based methods: (J) Cabello et al [214], (K) Juttukonda et al [215], (L) Ladefoged et al [216]. Graphical analyses methods include the Gjedde-Patlak equation [251,252], which describes irreversibly bound tracers, such as [ 18 F]FDG and the Logan-plot, which can be used to describe the reversibly bound tracers [253].…”
Section: Kinetic Modeling and Image Derived Input Function (Idif)mentioning
confidence: 99%
“…The creation of such parametric images can be divided into [208], (E) Anazodo et al [209], (F) Izquierdo-Garcia et al [210], (G) Burgos et al [211], (H) Merida et al [212]; MLAA-based methods: (I) Benoit et al [213]; Segmentation-based methods: (J) Cabello et al [214], (K) Juttukonda et al [215], (L) Ladefoged et al [216]. Graphical analyses methods include the Gjedde-Patlak equation [251,252], which describes irreversibly bound tracers, such as [ 18 F]FDG and the Logan-plot, which can be used to describe the reversibly bound tracers [253].…”
Section: Kinetic Modeling and Image Derived Input Function (Idif)mentioning
confidence: 99%
“…Even if the classification of the bone/ soft-tissue component is completely precise, the PET bias is within 610% in one study and is 4.0% 6 3.7% in the other study (11,31). Also, several studies revealed that adding the continuous bone attenuation value calculated from T2 relaxation time using dual UTE sequences contributes to improve AC (9,10,31).…”
Section: Discussionmentioning
confidence: 99%
“…The first family is that of template-/atlas-/model-based approaches (5)(6)(7). The second one is that of segmentation approaches (8)(9)(10)(11)(12). The third one constitutes methods directly estimating attenuation information from emission data (13,14).…”
mentioning
confidence: 99%
“…Thus, the most widely used clinical PET/MRI system (Biograph mMR; Siemens Healthcare) offers the UTE-based MR-AC along with the Dixon-based method for brain PET/MRI studies. However, the initial versions of the UTE sequence (i.e., mMR software version VB18P) yielded frequent segmentation errors at the boundary between soft tissue, bone, and air, and misclassification of the ventricle as air (33)(34)(35). Although a recent upgrade of the software from VB18P to VB20P offers more reliable attenuation maps than before, significant segmentation errors in the regions around the inferior part of the brain (i.e., sinus and lower skull structures) still exist.…”
mentioning
confidence: 99%
“…Although a recent upgrade of the software from VB18P to VB20P offers more reliable attenuation maps than before, significant segmentation errors in the regions around the inferior part of the brain (i.e., sinus and lower skull structures) still exist. Moreover, considerable quantification errors because of the inaccurate UTE MR-AC have been reported in several articles (33)(34)(35).…”
mentioning
confidence: 99%